Associations between neighborhood built environment and cognition vary by apolipoprotein E genotype: Multi-Ethnic Study of Atherosclerosis. (November 2019) - Besser, Lilah; Galvin, James E.; Rodriguez, Daniel; Seeman, Teresa; Kukull, Walter; Rapp, Stephen R.; Smith, Jennifer
Abstract: We examined whether neighborhood built environment (BE) and cognition associations in older adults vary by apolipoprotein E (APOE) genotype, a genetic risk factor for Alzheimer's disease (AD). We conducted a cross-sectional analysis of 4091 participants. Neighborhood characteristics included social and walking destination density (SDD, WDD), intersection density, and proportion of land dedicated to retail. Individuals were categorized as APOE ε2 (lower AD risk), APOE ε4 (higher AD risk), or APOE ε3 carriers. Among APOE ε2 carriers, greater proportion of land dedicated to retail was associated with better global cognition, and greater SDD, WDD, intersection density, and proportion of land dedicated to retail was associated with better processing speed. These associations were not observed in APOE ε3 or ε4 carriers. APOE ε2 carriers may be more susceptible to the potentially beneficial effects of denser neighborhood BEs on cognition; however, longitudinal studies are needed. Highlights: Apolipoprotein E (APOE) genotype modified buiit environment-cognition associations. Specifically, associations generally seen in APOE ε2 but not ε3 or ε4 carriers. In ε2 carriers, denser built environments associated with better cognition.